Real-Time Prediction for Burn Length of Stay Via Median Residual Hospital Length of Stay Methodology - Taylor, Sandra L. (J Burn Care Res, 2016)
Hospital length of stay (LOS) after burn injury is commonly estimated at one day per percent burn but LOS often exceeds that estimate. The study purpose is to develop a novel method for estimating burn hospital LOS at any time during hospitalization. We used the ABA National Burn Repository (NBR) from 2000–9 to directly estimate the median residual hospital length of stay (MRLOS) of patients hospitalized for burn injuries and who survived to discharge. The MRLOS is the median of how many more days a burn patient will be hospitalized given that the person has been in-hospital for a specified time period. We also estimated the 25(th) and 75(th) percentiles of residual length of stay and quantified the relationship between MRLOS and LOS with ordinary least squares for all burn patients, by burn size and by presence of inhalation injury. MRLOS increased with increasing LOS confirming that discharge estimates change over time. Patients with inhalation injury had longer MRLOS than patients without inhalation injury in the first 100 hospital days. Patients with large burns (>25%) had large MRLOS consistent with prolonged hospitalization, but patients with small burns (<25%), also had steadily increasing MRLOS during hospitalization (i.e. the longer the patient was in the hospital, the longer the predicted LOS regardless of initial LOS estimate). Estimating remaining hospital LOS at any time during admission has been problematic; MRLOS can be used to provide an estimate of remaining hospital LOS and resource utilization to families, administrators, and other medical professionals.